2014
DOI: 10.1136/neurintsurg-2014-011327
|View full text |Cite
|
Sign up to set email alerts
|

Posterior communicating and vertebral artery configuration and outcome in endovascular treatment of acute basilar artery occlusion

Abstract: Reperfusion emerged as a predictor of good outcome in patients that underwent IAT for BAO. Angioarchitectural variations of the posterior circulation were not found to impact reperfusion or clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…26 Others have not been able to show a relationship between PCoA size and outcome in IAT treated patients with a BAO. 27 Although the BASICS registry is the largest prospective registry of consecutive patients with an acute BAO, the observational design inherently has limitations. First, with 149 patients included in the current study the sample size is still small.…”
Section: Discussionmentioning
confidence: 99%
“…26 Others have not been able to show a relationship between PCoA size and outcome in IAT treated patients with a BAO. 27 Although the BASICS registry is the largest prospective registry of consecutive patients with an acute BAO, the observational design inherently has limitations. First, with 149 patients included in the current study the sample size is still small.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating the effect of PcoA in the outcome of brain stem infarcts are conflicting. One study investigating basilar artery occlusion infarcts provided no relation of PcoA hypoplasia or vertebral artery configuration with functional outcome (24). Another study, on the other hand, showed an association between PcoA hypoplasia and poor functional outcome at the end of 1st month (25).…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical variation of the vertebrobasilar system is very common, which may contribute to the associated morbidity of the VA pseudoaneurysm development and treatment [ 17 ]. Asymmetry due to a unilateral hypoplastic VA, extracranial VA occlusion, or VA ending in the posterior inferior cerebellar artery (PICA) may result in increased reliance on the contralateral VA.…”
Section: Discussionmentioning
confidence: 99%